2009
DOI: 10.1016/j.breast.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Results of tailored treatment for breast cancer patients with internal mammary lymph node metastases

Abstract: Although the internal mammary (IM) lymph node status is a major prognostic factor in breast cancer, IM nodal staging is not common practice. In order to improve nodal staging, we have routinely performed IM sentinel node (SN) biopsy and have adjusted adjuvant treatment accordingly. We reviewed the outcome of these patients. Data from 764 patients were available for follow-up. A total of 406 patients had no lymph node metastases (group 1), 330 patients had axillary metastases (group 2), 7 patients had IM metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…We selected 6 studies that fulfilled the following criteria: a large number of patients, peritumoral or intratumoral tracer injection, internal mammary biopsy successfully achieved in most patients with internal mammary drainage, and axilla staged routinely independent of internal mammary status (47)(48)(49)(50)(51)(52).…”
Section: Probability Of Internal Mammary Involvement In Patients Withmentioning
confidence: 99%
“…We selected 6 studies that fulfilled the following criteria: a large number of patients, peritumoral or intratumoral tracer injection, internal mammary biopsy successfully achieved in most patients with internal mammary drainage, and axilla staged routinely independent of internal mammary status (47)(48)(49)(50)(51)(52).…”
Section: Probability Of Internal Mammary Involvement In Patients Withmentioning
confidence: 99%
“…Eventually, 15 articles met the inclusion criteria [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27], containing a total of 4,248 breast cancer patients who underwent IML node dissection. The number of patients ranged from 30 to 1,213 for each study and the average age was from 47 to 61 years.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical treatment alone cannot improve the patients' survival rate [45,46]. In 2009, Heuts et al [26] reported that internal mammary sentinel node (IMSN) biopsy changed the adjuvant systemic treatment in 7 IML node-positive patients. 5 of them were axillary node negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advances in the sentinel lymph node biopsy (SLN) procedure have led to a re-evaluation of the role of the SLN for staging IMLN basin [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In addition, few recent clinical trials demonstrate that post-mastectomy irradiation of IMLNs significantly improved the metastasis-free overall survival of patients with stage I-III breast cancer [34][35][36].…”
Section: Introductionmentioning
confidence: 99%